Pengetahuan lokal berbasis masyarakat adat untuk pengelolaan tanaman masohi: pembelajaran dari Distrik Teluk Patipi Kabupaten Fak-Fak - Arnoldus Tuturop; Julis D Nugroho; Hendri (Cassowary, 2022)
Masohi bark is a primadonna product other than in Fak-Fak Regency, therefore it is necessary to study the preservation and development of masohi plants. Masohi has been developed based on local knowledge based on indigenous peoples. Survey method by exploring key figures related to land history, cultivation techniques, harvesting, and processing masohi bark. Furthermore, these data were analyzed using a Likert scale and showed that the role of indigenous peoples was still very high. The results showed that community seed gardens helped a lot in providing quality seeds with maintenance, prioritizing organic fertilizers, some harvesting of masohi bark was still being cut down, and problems with drying when wet conditions. In addition, it was also found that their management is still not based on technology and adaptation to climate change. Several strategic proposals are needed for further development for the parties so that sustainable management can still be sustainable in terms of quantity and quality.